Novel methods in diagnosis of endometriosis in future - Devi, T. Ramani; Kadalmani, Balamuthu; Devi, C. Anchana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Endometriosis causes severe pain and infertility affecting quality of life. According to ASRM it is a chronic inflammatory disease that requires life-long management plan and surgery has to be restricted only once in the life time of the patient. Earlier, the diagnosis of endometriosis was confirmed by surgical method and histo-pathological examination. There is often a diagnostic delay up to 7 years or even beyond, which will affect the patients getting earlier treatment. Recently, lot of non-invasive techniques for diagnosis of endometriosis have come into vogue so that, treatment can be planned without surgical diagnosis. Apart from imaging through USG, CT or MRI, earlier lesions can be picked up by biomarkers like IL-6, IL-8, CA 125, HE4, neutrophil-lymphocytic ratio, Hs-CRP, Tumour necrosis alpha and mi RNA, neural elements in endometrium, glyco-proteins like CA-125, CA-19.9, CA-15.3, CA-73, AFP and CEA. Urocortin, activin and follistatin are growth factors and VEGF, TNF-alpha, NK cells, i-SCAM-I, MCP-1 are immunologic markers for diagnosis of endometriosis. Circulating endometrial cells are also present in the peripheral blood of patients. miRNA in endometriosis is found to be a potential biomarker in the recent years and also associated with altered vaginal microbiome. There has been up-regulation and down-regulation of certain miRNAs in endometriosis patients. In patients with symptoms of endometriosis, miRNA study in peripheral blood can be used as a biomarker for confirmation of diagnosis. There is a strong association between mitochondrial DNA variation and endometriosis which is found to be rational biomarkers.